2002
DOI: 10.1046/j.1396-5883.2001.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuing professional development amongst dental practitioners in the United Kingdom: how far are we from lifelong learning targets?

Abstract: This study was conducted to identify the extent to which qualified dental practitioners in the UK currently undertake three distinct activities of Continuing Professional Development (CPD): reading professional journals; attending courses; and undertaking retraining courses. Also, to determine the impact of gender, age, length of time since qualification, current working hours and career breaks upon the extent to which dental practitioners engage in CPD. Data were analysed from a questionnaire survey of a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2008
2008
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 8 publications
1
31
0
1
Order By: Relevance
“…Male dentists were also more active in other forms of continuing education, as indicated by memberships of dental societies, regularity of reading dental journals and attendance at formal continuing professional development than their female colleagues. Recent UK findings are not clear as to whether women read professional journals less frequently than men, 19,24 although female dentists have been reported to spend less time at continuing education courses than males. 24 This is of concern as dentists who do not attend continuing education sessions are at increased risk of professional isolation.…”
Section: Continuing Educationmentioning
confidence: 98%
“…Male dentists were also more active in other forms of continuing education, as indicated by memberships of dental societies, regularity of reading dental journals and attendance at formal continuing professional development than their female colleagues. Recent UK findings are not clear as to whether women read professional journals less frequently than men, 19,24 although female dentists have been reported to spend less time at continuing education courses than males. 24 This is of concern as dentists who do not attend continuing education sessions are at increased risk of professional isolation.…”
Section: Continuing Educationmentioning
confidence: 98%
“…half-day, full-day) differ or are not specified. Furthermore, although the majority of these studies looked at courses undertaken in the previous year (4,25,31,33,34,(39)(40)(41)43), some looked over a 2-year period (28,29,35,36) and one considered intentions (10). Review of CPD for dentists Barnes et al To understand more about the reasons for the variation in engagement with CPD, studies that reported factors relating to CPD uptake were scrutinised.…”
Section: Continuing Professional Development Uptakementioning
confidence: 99%
“…13 These results are similar to those of Buck and Newton, who found that a large proportion of dental practitioners were currently undertaking sufficient CPD to satisfy the UK General Dental CouncilÕs proposed requirements for recertification. 14 The aims of this study were to: (1) determine attitudes to CPD amongst registered Victorian dental personnel; (2) determine participation in various forms of CPD by registered Victorian dental personnel, including perceived barriers to participation; and (3) determine attitudes to the DPBVÕs Code of Practice on CPD by registered dental personnel.…”
mentioning
confidence: 99%